2007
DOI: 10.1073/pnas.0705250104
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal hydrogels

Abstract: Fungi are increasingly identified as major pathogens in bloodstream infections, often involving indwelling devices. Materials with antifungal properties may provide an important deterrent to these infections. Here we describe amphogel, a dextran-based hydrogel into which amphotericin B is adsorbed. Amphogel kills fungi within 2 h of contact and can be reused for at least 53 days without losing its effectiveness against Candida albicans. The antifungal material is biocompatible in vivo and does not cause hemoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(70 citation statements)
references
References 26 publications
2
68
0
Order By: Relevance
“…Nevertheless, 1 M simvastatin is still ϳ30-fold higher than the plasma level achieved after standard oral dosing in humans (28). Although pharmacoepidemiologic studies have found no increased risk for fetal anomalies in pregnant women taking statins (45), reformulating simvastatin as a coating for catheter lumens may be a more feasible approach, as has been done with other substances such as EDTA or amphotericin, where oral dosage is impractical (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, 1 M simvastatin is still ϳ30-fold higher than the plasma level achieved after standard oral dosing in humans (28). Although pharmacoepidemiologic studies have found no increased risk for fetal anomalies in pregnant women taking statins (45), reformulating simvastatin as a coating for catheter lumens may be a more feasible approach, as has been done with other substances such as EDTA or amphotericin, where oral dosage is impractical (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Our group developed a rabbit model of catheter-associated C. albicans biofilm infection ( 41 ) and showed that 7 days postinfection, quantitative catheter cultures consistently yielded >2 log CFU/catheter segment, which is considered the threshold for catheter-related infections. We also used a subcutaneous mouse model to evaluate the effect of coating a catheter substrate with amphogels (amphotericin B–based gel) on Candida biofilms ( 42 ) and demonstrated that the subcutaneous model has utility in studies evaluating catheter surface modification on the ability of Candida to form biofilms.…”
Section: Experimental Models Of Candida Biofilmsmentioning
confidence: 99%
“…A number of strategies such as polymeric and peptide hydrogels, nanoparticles, microemulsion, liposomes, niosomes, or ethosomes that can function as drug depots for delivering the antifungals at the site of infections have been reported. [15][16][17][18][19][20] However, these formulations need to be applied frequently to maintain sustained release of the drugs. 21 Nonwoven fiber mats produced by electrospinning have the potential for a wide range of applications such as filters, composites, drug carriers, wound dressing, and tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%